Robust Quality Control Implementation for Nickel Pig Iron Using Median Absolute Deviation Estimators - Aditya Rahadian Fachrur; Chyntia Devi Octaviany; Wiwien Suzanti; Midia Rahma; Mariana Feronica Damanik; Ferdian Bangkit Wijaya (Theta: Journal of Statistics, 2025)
Nickel Pig Iron (NPI) is one of the main products of Indonesia's nickel-based industry, which is still expanding. Reducing production costs and guaranteeing product quality depends on maintaining a constant nickel content. The Median Absolute Deviation (MAD) estimator, which is resistant to outliers and non-normal distributions, is used in this study's control charts and process capability analysis. After 15 days of production, data was gathered and examined using capability indices and control charts based on MAD. According to the results, the process mean is not statistically in control since many points exceed the control borders, even while process variation stays within the control limits. Acceptable process precision was indicated by the process capability index CpMAD being above 1. However, the CpkMAD value below 1 suggests that the mean process output does not consistently meet the target specifications. These findings highlight the need for further investigation and process improvement to enhance quality consistency in NPI production.